Homœopathy and disability - Vickers, Andrew (British Homeopathic Journal, 1993)
The classification of disability is outlined. The limitations of the medical model when applied to disability and the practical problems of disabled people are discussed. The literature on homœopathic treatment of disability is reviewed. The basic causes of disability are often irreversible, but homœopathy may have an important role to play in the relief of secondary symptoms. Homœopathic treatment of people with disabilities, especially children, requires further study.
Keywords: Disability; Physical disability; Sense impairment; Learning disability; Homœopathy; Literature review; Secondary symptoms